Pertumbuhan dan kelangsungan hidup larva gurami (Osphronemus gouramy) dengan pemberian beberapa jenis pakan - Lucas, Weismann G.F; Kalesaran, Ockstan J; Lumenta, Cyska (e-Journal BUDIDAYA PERAIRAN, 2015)
This study aimed to determine the effect of several different types of feed on absolute length growth, relative length growth, and survival rates are gouramy larvae (Osphronemus gouramy). This study used four treatments, with three replications. The treatments tested were four different types of feed on the larvae of gouramy, among others; feed worms Tubifex sp., Artemia sp.,boiled chicken egg yolk and finely pelleted feed FF-999. The experimental design used was completely randomized design.      The results showed that different types of feed provided a significant influence on the absolute length growth, relative length growth and survival of larval gouramy (Osphronemus gouramy). Feed worms Tubifex sp. give the best results with an absolute value growth of 1.34 cm length, relative length of 148.87% growth, and survival of 34%. Feed worms Tubifex sp. is the best feed in promoting growth and improving survival of larval gouramy (Osphronemus gouramy).   Keywords : Larvae,  gourami, Tubifex, Artemia, feed